2021
DOI: 10.3390/brainsci11020263
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Reading Modulation: Temporo-Parietal tDCS Alters Visuo-Spatial Attention and Motion Perception in Dyslexia

Abstract: Dyslexia is a neurodevelopmental disorder with an atypical activation of posterior left-hemisphere brain reading networks (i.e., temporo-occipital and temporo-parietal regions) and multiple neuropsychological deficits. Transcranial direct current stimulation (tDCS) is a tool for manipulating neural activity and, in turn, neurocognitive processes. While studies have demonstrated the significant effects of tDCS on reading, neurocognitive changes beyond reading modulation have been poorly investigated. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 95 publications
2
31
0
1
Order By: Relevance
“…The results showed a significant improvement in text reading accuracy for a bilateral montage with left anodal/ right cathodal tDCS (i.e., facilitating the left and inhibiting the right TPC), as well as an increase in errors after left cathodal/right anodal TPC stimulation. This study served as basis for the earlier presented multiple session interventions.Most recently, Lazzaro et al further investigated a tDCS-induced modulation of reading performance, while at the same time assessing other reading-relevant processes, such as motion perception and visuo-spatial working memory(Lazzaro et al, 2021). Left anodal/right cathodal tDCS of the left TPC (as in previous studies) improved text reading accuracy, word recognition and motion perception.…”
mentioning
confidence: 89%
“…The results showed a significant improvement in text reading accuracy for a bilateral montage with left anodal/ right cathodal tDCS (i.e., facilitating the left and inhibiting the right TPC), as well as an increase in errors after left cathodal/right anodal TPC stimulation. This study served as basis for the earlier presented multiple session interventions.Most recently, Lazzaro et al further investigated a tDCS-induced modulation of reading performance, while at the same time assessing other reading-relevant processes, such as motion perception and visuo-spatial working memory(Lazzaro et al, 2021). Left anodal/right cathodal tDCS of the left TPC (as in previous studies) improved text reading accuracy, word recognition and motion perception.…”
mentioning
confidence: 89%
“…Consistent with the hypothesis of a right posterior parietal dysfunction in dyslexia (e.g., Hari et al, 1999 ; Facoetti et al, 2001 ), some studies observed deficient activations in the right TPJ in dyslexics when performing phonological decoding tasks (e.g., Hoeft et al, 2006 ). Moreover, a very recent study ( Lazzaro et al, 2021 ) has shown significant effects of tDCS on temporo-parietal regions either on reading performance as on visuo-spatial skills of dyslexic children and adolescents. Overall, the findings of the present study endorse this hypothesis by showing that the mechanisms of rapid orienting of spatial attention are impaired in adults with DD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in dyslexic children and adolescents have shown that a treatment with tDCS causes improvement in reading skills and reduction in word reading errors and wordless reading time gap 80–83 . A study in 10 dyslexic children further demonstrated that the application of anodal tDCS improved text accuracy, word recognition speed, motion perception, and attentional focusing 84 . In addition, tDCS stimulation combined with training for reading in children and adolescents with dyslexia produced long‐lasting improvement in reading 85 .…”
Section: Non‐invasive Brain Stimulationmentioning
confidence: 99%